2004
DOI: 10.1021/ja036732j
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized Molecular Propellers by Cyclodehydrogenation of Polyphenylene Dendrimers

Abstract: In a polymer analogous approach, large dendritic oligophenylenes containing benzene and tetraphenylmethane cores are transformed via oxidative cyclodehydrogenation to novel propeller-shaped molecules with large polycyclic aromatic hydrocarbon units as "blades". Structure analysis is performed by a combination of MALDI-TOF mass spectrometry, UV/vis, fluorescence, and Raman spectroscopy using solid-state sample preparation methods. These methods are also utilized to determine the degree of the cyclodehydrogenati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
97
0
7

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(105 citation statements)
references
References 19 publications
1
97
0
7
Order By: Relevance
“…1c. Briefly, it is based on a polymerization of pre-synthesized molecular precursors by a Ni 0 -mediated Yamamoto coupling 45 followed by a cyclodehydrogenation via a Scholl reaction using iron (III) chloride 46 to form GNRs. This synthetic approach is described in detail in the Methods section.…”
Section: Synthesis Of Gnrsmentioning
confidence: 99%
“…1c. Briefly, it is based on a polymerization of pre-synthesized molecular precursors by a Ni 0 -mediated Yamamoto coupling 45 followed by a cyclodehydrogenation via a Scholl reaction using iron (III) chloride 46 to form GNRs. This synthetic approach is described in detail in the Methods section.…”
Section: Synthesis Of Gnrsmentioning
confidence: 99%
“…In diesen Fällen schlugen die Autoren die Entstehung dreidimensionaler propellerförmiger Strukturen vor. [150] Einige einfachere Vertreter funktionalisierter PAKs wurden auf ihr Potenzial getestet, als Vorstufenmoleküle für nanostrukturierte Kohlenstoffmaterialien zu dienen. Auf diese soll in Abschnitt 5 detailliert eingegangen werden.…”
Section: Schema 2 Synthese Eines [N]-paraphenylen-makrocyclus Durchunclassified
“…These are grinding by mortar and pestle [4,5], ball-mill [1][2][3][4], and vortexing [6]. Analyte, matrix, and salt are added to a vessel and, in the case of the ball-mill or vortex methods, suitably sized balls are used to assist in the homogenization process.…”
mentioning
confidence: 99%
“…A significant advantage of solventfree MALDI analysis is that the method is capable of characterizing insoluble compounds such as polyfluorene [1] and is consequently routinely used for the characterization of large polycyclic aromatic hydrocarbons [2]. A recent study based on the ball-mill homogenization/loose powder transfer method revealed that solvent-free MALDI-MS simplifies the measurement and improves the result qualitatively and quantitatively [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation